The Role of Family in Improving Adherence to Anemia Treatment in Pregnant Women: A Case Study in Labulia Village (Journal of Social And Education Research, 2025)
Anemia during pregnancy is a common health issue that poses significant risks to both maternal and fetal health, particularly in the third trimester. This study aims to explore the role of family involvement in improving adherence to anemia treatment in pregnant women. Using a case study approach, the research was conducted in Labulia Village from August 29 to September 25, 2024, focusing on a 25-year-old pregnant woman diagnosed with severe anemia in her third trimester. Data were collected through in-depth interviews, direct observation, and clinical assessments, including hemoglobin levels, vital signs, and dietary intake. The study found that family support played a crucial role in enhancing the mother's understanding of anemia, leading to improved compliance with prescribed iron supplementation and dietary recommendations. The results showed a significant increase in hemoglobin levels from 8.0 g/dL to 11.8 g/dL, demonstrating the effectiveness of both education and family involvement in managing anemia. This case study underscores the importance of integrated maternal health education and the critical role of family support in preventing pregnancy-related complications, particularly anemia in the third trimester.